ASSESSING THE EFFECTIVENESS OF EDUCATIONAL BROADCASTING IN 21ST CENTURY NIGERIA: EVIDENCE FROM EBBC TELEVISION - Cosmas Nwoga, Chibuzor; Obin Obin, Ogban; Chinemerem Ibe, Kingsley; Ononuju Nwankiti, Chukwuemeka; Rose Chime-Nganya, Chioma; Lynda Ngwu, Ogonnaya (African Journal of Social and Behavioural Sciences, 2026)
This study assessed educational broadcasting in Nigeria amidst the challenges of the 21st century, with a focus on EBBC TV educational programmes. The objectives were to ascertain EBBC’s preparedness level for educational broadcasting; assess the level of awareness, efficacy and reach of EBBC educational broadcasting; ascertain the implications of educational broadcasting on the development of Ebonyi State; and investigate the quality of curriculum used in EBBC programmes. This study adopted a survey design and was anchored on the Diffusion of Innovation theory. A sample size of 400 was drawn using Taro Yamane’s method, and data were collected from 385 respondents to explore their perceptions and experiences with EBBC TV educational content. Findings revealed that the level of preparedness of the EBBC for educational broadcasting is rather low. Despite the acceptable relevance, the awareness and reach of EBBC’s educational broadcasts are still low; there are positive implications for Ebonyi State if utilised; and, invariably, EBBC has not been making use of the State’s educational curriculum in designing its educational programmes. It was recommended that the station’s preparedness level for the educational broadcasting should be heightened through funding, and provision of digital broadcast equipment; enhanced accessibility through digital literacy programmes, improving content through collaboration with educational institutions, and leveraging emerging technologies for better dissemination; stakeholders in education and broadcasting should work in synergy to enhance the effectiveness of educational broadcasting in Ebonyi; and there is need to collaborate with subject experts to ensure quality and engaging educational contents that meet curriculum standards.